A new species of Psychotria (Rubiaceae) from Bidoup - Nui Ba National Park, Vietnam - Nguyen, Quoc Bao; Quach, van Toan Em; Huynh, Huu Duc; Pham, Quoc Trong; Truong, Ba Vuong; Yahara, Tetsukazu; Tagane, Shuichiro; Dang, Van-Son (Phytotaxa, 2023)
A new species, Psychotria ngotphamii (sect. Psychotrieae), is described and illustrated from Bidoup - Nui Ba National Park, Lam Dong Province, Vietnam. Psychotria ngotphamii is most similar to P. bonii Pit. but distinguished by its smaller leaf blades, shorter petioles, longer calyx and corolla lobes, and larger fruits. Photographs, vernacular name, preliminary conservation assessment, and a table comparing P. ngotphamii with its closest allies are provided.